Perception of Prickliness in Fabrics made with Dehaired and Non-Dehaired Llama Fiber and its Relationship with Fiber-Based Variables detected by Consumers - Frank, Eduardo (2020)
The prickling is a problem in natural animal fiber, but there is no an allergic but a mechanical problem. In this manner, dehairing is a pre-textile process that permit extract objectionable (coarse) fiber and then improve the fabric quality. The objective of this study is to determine the variables of the fiber diameter and fiber frequency may be indicative of the effect of the dehairing on prickliness of Llama fiber fabrics that can be detected by consumers of knitting fabric garments. The variables that panellists consumers can detect when comparing dehaired and non-dehaired fibres are: overall fibre diameter (in fabric and surface), fibre diameter coefficient of variation (significate in yarn); fibres coarser than 30 μm (in yarn and surface); coarse fibre by weight (in yarn and in surface); coarse fibre mean diameter (in yarn and in surface). These differences are explained mainly by the lattice medulated fibre diameter (in yarn and in fabric surface); non-medulated fibre diameter (only in surface); and lattice medulated fibre frequency (only on fabric surface). It can conclude that: the variables that indicate differences in the frequency of coarse fibres (objectionable) are the ones that best indicate the prickle (itching) effect, both inside the yarn and in the protruding fibre tips on fabric surfaces.